Designing environment-friendly chromium-free Spinel-Periclase-Zirconia refractories for Ruhrstahl Heraeus degasser - Mandal S.; Dileep Kumar C.J.; Kumar D.; Syed K.; Van Ende M.-A.; Jung I.-H.; Finkeldei S.C.; Bowman W.J. (My University, 2025)
Ruhrstahl Heraeus (RH) degassers are globally used to manufacture vacuum-treated steel for automotive and railroad applications. The state-of-the-art environment-friendly chromium-free alternatives for direct-bonded magnesia-chrome refractories used in RH degassers are expensive, and the scientific literature lacks direct correlation between materials chemistry, processing, and functional properties. We have designed a novel spinel-periclase-15 wt% ZrO2 composition containing 14 wt% in situ spinel which exhibited 7.2 MPa hot modulus of rupture (1500℃), exceeding all reported Cr-free refractories for RH degasser applications. Investigation with scanning electron microscopy coupled with energy dispersive spectroscopy (SEM-EDS) attributed this improvement to a reduction in interparticle Ca and Si content which forms low-melting phases, as supported by FactSage thermodynamic simulations. The spinel-periclase composition SP exhibited superior thermal shock resistance because thermal shock-induced cracks were stopped by fracture porosity around MgO particles, formed due to thermal expansion mismatch. SEM-EDS analysis of the SP composition corroded by RH slag at 1650°C revealed that Fe is the most corrosive element followed by Ca and Si. Contradicting the consensus, it was observed that corrosion resistance of fused MgO was better than that of ZrO2. The cubic ZrO2 phase reduced FeOx penetration locally by incorporating CaO from the RH slag into a solid solution and forming a CaZrO3 phase creating a “slag barrier”. Lastly, pore size was found to greatly exacerbate slag penetration following the Washburn percolation model. © 2020 American Ceramic Society (ACERS)